Analisis Hak Anak berdasarkan Teori Kebutuhan Maslow Dan Undang-Undang Nomor 35 Tahun 2014 - Wibisono, Eko; Ahmad Fiqrie, Al Husen; Agung, Heru Rahayu; Japar, Muhammad; Kardiman, Yuyus (Universitas Muhammadiyah Ponorogo, 2026)
According to Law Number 35 of 2014, a child is a human being under the age of 18. The number of children in Indonesia is very large, reaching 88,819,900 people or 31.23% of the total population in Indonesia based on the census conducted by the Central Statistics Agency. The large number of children in Indonesia makes children a determinant of the country's progress in the future, regarding the needs and rights of every child in Indonesia that must be considered. In reality, providing children's rights has not been running optimally. According to data released by the Ministry of Women's Empowerment and Child Protection in 2024 there were 25,559 cases of violence against children throughout Indonesia. Meanwhile, according to the Ministry of Primary and Secondary Education, by 2025 there were 3.9 million children who were not in school. Abraham Harold Maslow, a psychologist from New York, put forward the Theory of Levels of Needs which explains five levels of human needs in general and has a similar view to Law Number 35 of 2014 which explains children's rights. This research uses a qualitative method with a literature study approach and was conducted on October 27 – November 17, 2025.